Dampak Kurangnya Komunikasi Orang Tua Terhadap Kesulitan Sosial Anak di Masa Remaja - Siti Fatimah; Ilah Holilah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Communication between parents and children plays a crucial role in shaping children’s social skills, especially when entering adolescence. Lack of effective communication can cause various social difficulties, such as low self-confidence, difficulty adapting to new environments, and problems in buiding interpersonal relationships. This study aims to analyze the impact of lack of parental communication on social difficulties experienced by adolescents. The results of the study showed that adolescents who lack open and supportive communication from their parents tend to have difficulty expressing emotions, interacting with peers, and dealing with social pressure. The conclusion of this study emphasizes the importance of warm and open communication between parents and children to support healty social development during adolescence. Research method with a qualitative approach, with case studies, conducted through in-depth interviews with several teenagers who experience social difficulties due to lack of communication with their parents.